PERAN KEPALA SEKOLAH DALAM PELAKSANAAN MANAJEMEN BERBASIS SEKOLAH UNTUK MENINGKATKAN KINERJA GURU - Qathratun Nada, Annisa; Fadlizon Julian; Hadiyanto, Hadiyanto; Nurhizrah Gistituati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research examines the role of school principals in implementing school-based management (SBM) to improve teacher performance. School-based management is a decentralized approach that gives schools greater autonomy in decision-making, with the aim of improving the quality of education. The principal plays a key role as a leader and manager in the implementation of SBM, which involves planning, organizing, directing and supervising. This research uses qualitative methods with interview and observation techniques to collect data from several schools. The research results show that school principals who are effective in implementing SBM have strong leadership abilities, good communication, and skills in managing resources. In addition, the principal’s support in teacher professional development, strengthening positive school culture, and providing constructive feedback has been proven to increase teacher motivation and performance. In conclusion, the role of the school principal is very important in implementing SBM and has a significant impact on improving teacher performance, which ultimately contributes to improving the quality of education in the school.